Comparison growth of Candida albicans in alternative media and semi-synthetic on fisheries cerumen in bastiong karance Ternate City - erpi nurdin (International Journal of Applied Biology, 2020)
Otomycosis is an inflammatory process in the ear canal caused by a fungal infection. The activity of fishermen on the high seas at night or during the day is often at risk of contracting fungal diseases, because their workplaces are in the open air and in wet and humid areas favored by fungi. Work as a fisherman also makes them often exposed to direct sunlight so that the body's temperature rises, the body will produce sweat and cause the ear wax to be disturbed. Semi-synthetic media such as PDAs have sufficient carbohydrate content so that they are good for fungal growth. This media is pretty much needed in fungal breeding both in the laboratory and in agriculture. But the price of this media is quite expensive besides that not all chemical shops provide it, while the needs of PDA media are increasing so that another alternative is needed to replace the fungal culture media. This research is instrumental with a cross sectional approach and aims to find out the level of significance of the differences in the growth of Candida albicans against alternative media for agar dextrose agar and semi-synthetic Potato Dextrose agar (PDA). The sampling technique was non-random with a purposive sampling design of 46 people. The sample was then isolated on a semi-synthetic PDA media and alternative media to see differences in the growth of Candida albicans. Based on the research that has been carried out, it is concluded that there are 38 samples of respondents detected positively Candida albicans on semi-synthetic media (PDA) and alternative media, and based on the results of data processing obtained p value 0,000 <0.05 which indicates that there are very significant differences in growth Candida albicans between semi-synthetic media (PDA) and alternative media.Keyword : Candida albicans, Alternative Media, Potato Dextrose Agar.